Transaksi Jual Beli dengan Bitcoin Perspektif Fiqh Muamalah - Nani Feliyani; Muhammad Hery Ardiyanto (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
Bitcoin is an online payment system of peer-to-peer electronic money that is sent directly from one party to another without going through a financial institution. Bitcoin has characteristics as a currency or medium of exchange because it is accepted as a means of payment by its community. However, there will be a lot of hope that can happen to bitcoin users, namely because bitcoin is al-jahalah (unclear) will cause an element of fraud in buying and selling with bitcoin. So the purpose in this study is to find out how fiqh review is muamalah on buying and selling transactions with bitcoin. This research is qualitative literature (library research). Data collection methods use documentation and data analysis using deductive analysis techniques. The results of this study show that the practice of buying and selling with bitcoin is either aimed at the needs of exchange tools or investment businesses, especially in online financial transactions including from syubhat, and something that syubhat should be abandoned, because it does not bring benefits at once that is the purpose of Islamic sharia, namely its own benefits will not be realized.